A hollow three-dimensional porous silicon material and a preparation method thereof

The use of magnesium silicide in a controlled ball-milling and calcination process addresses the issues of high heat release and low yield in traditional magnesium thermal reduction, producing a hollow three-dimensional porous silicon material with improved cycle stability and capacity for lithium-ion batteries.

CN115893420BActive Publication Date: 2024-12-13JIESHOU HUAYU POWER SUPPLY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211139164.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-19
Publication Date
2024-12-13
Estimated Expiration
2042-09-19

AI Technical Summary

Technical Problem

Existing magnesium thermal reduction methods for producing porous silicon materials in lithium-ion batteries suffer from high heat release, sintering, low yield, and environmental pollution, making them unsuitable for commercial applications.

Method used

A method using magnesium silicide as a reducing agent to produce a hollow three-dimensional porous silicon material with a three-dimensional porous shell structure, achieved through ball-milling silicon dioxide and magnesium silicide, followed by calcination and acid washing to form a porous structure on both inner and outer surfaces, maintaining the spherical morphology of silicon dioxide.

Benefits of technology

The method results in a porous silicon material with improved cycle stability and high capacity, achieving a specific surface area of 100-200 m²/g and a particle size of 0.5-10 μm, with a porous shell layer providing a buffer for volume expansion, enhancing the material's performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115893420B_ABST
    Figure CN115893420B_ABST
Patent Text Reader

Abstract

The present invention discloses a hollow three-dimensional porous silicon material and a preparation method thereof. Magnesium silicide is used as a reducing agent, mixed with silicon dioxide, ball-milled, and pickled to obtain a hollow silicon material with a complete or incomplete spherical, three-dimensional porous shell. The shell has a three-dimensional porous structure, which greatly increases the specific surface area of ​​the material and provides a buffer space for the volume expansion of the silicon material; the hollow structure can also provide a buffer space for the volume expansion of the silicon material during the circulation process, both of which are conducive to improving the cyclic stability of the silicon material. The method uses a new type of reducing agent to control the reaction heat and improve the yield of the silicon material, solving the problem of material sintering and agglomeration caused by the existing metal thermal reduction technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical negative electrode materials, and specifically to a hollow three-dimensional porous silicon material and a preparation method thereof. Background Art

[0002] Silicon material is the preferred negative electrode material for modern lithium-ion batteries, and has a higher capacity than graphite. However, the volume expansion of silicon material as a negative electrode material for lithium-ion batteries is very serious, which leads to its poor electrochemical performance and is not conducive to commercial application. Structural design of silicon materials is currently considered to be one of the more effective methods to improve the cycle stability of silicon materials. Structural designs include porous structures, hollow structures, coating structures, etc. These special structures can provide buffer space or effectively restrain the volume expansion of silicon materials, thereby improving the cycle stability of silicon materials.

[0003] Magnesium thermal reduction is one of the commonly used methods for preparing porous silicon. The reaction formula is:

[0004] SiO2(s)+2Mg(g)→Si(s)+2MgO(s)

[0005] However, this reaction has two major defects. First, magnesium thermal reduction is a typical exothermic reaction. The huge heat released during the reaction will cause the product Si to sinter and agglomerate, generating block silicon of dozens of microns. Although its microstructure is also porous, the huge particles of dozens of microns cause its circulation attenuation to be very serious. Second, SiO2 and Mg in this reaction cannot react in a molar ratio of 1 to 2. This is because excess Mg will react with the product Si to form an alloy, resulting in a reaction yield of only about 50%. At present, the main modification of the magnesium thermal reduction method by researchers focuses on using molten salt as a heat clearing agent to absorb part of the heat. However, it does not solve the problem of high heat release and low yield from the reaction itself.

[0006] Chinese patent application CN106058256A discloses a method for preparing a carbon nanotube composite porous silicon negative electrode material for lithium-ion batteries, which comprises fully mixing silicon dioxide and magnesium powder, and then performing a magnesium thermal reaction at 500-950 degrees Celsius under the protection of an inert atmosphere, which ultimately leads to sintering of the product. Summary of the invention

[0007] Purpose of the invention: The purpose of the present invention is to provide a hollow silicon material with a three-dimensional porous shell structure, which has a simplified and efficient preparation process, high capacity, and greatly improved cycle stability; another purpose of the present invention is to provide a preparation method for the aforementioned silicon material based on an improved magnesium thermal reduction process.

[0008] Technical solution: In order to achieve the above-mentioned invention purpose, the present invention provides a hollow three-dimensional porous silicon material, including an average particle size of 0.5-10 μm and a specific surface area of ​​100-200 m2 / g of hollow silicon, wherein the hollow silicon has a complete or incomplete spherical shell layer with an average thickness of 0.5-10 μm, and the shell layer is a three-dimensional porous structure.

[0009] The porous silicon material provided by the present invention can be nanometer-scale or micrometer-scale, and the biggest difference compared with the prior art is that the shell layer is a three-dimensional porous spherical pure phase Si. The prior art mostly uses metal thermal reduction method or acid-base etching method to obtain similar porous structures, but these methods generally have the defects of large heat release, environmental pollution, low yield, and difficulty in large-scale production.

[0010] As a further optimization of the present invention, the porous silicon material comprises an average particle size of 2-8 μm and a specific surface area of ​​120-150 m 2 / g of hollow silicon, wherein the hollow silicon has a complete or incomplete spherical shell layer with an average thickness of 0.5-7 μm.

[0011] Furthermore, through process improvement, hollow silicon with a mass percentage of 90-99% and oxygen with a mass percentage of 1-10% can be obtained, with an average particle size of 4-7 μm and a specific surface area of ​​120-150 m 2 / g of hollow silicon; the hollow silicon has a complete or incomplete spherical shell layer with an average thickness of 0.5-7 μm.

[0012] Based on the aforementioned hollow three-dimensional porous silicon material, the present invention also provides a lithium battery negative electrode, comprising a current collector coated with a slurry and dried, wherein the slurry comprises 80-98% of the aforementioned hollow three-dimensional porous silicon material, 0.1-10% of a conductive agent, and 0.1-10% of a binder by mass percentage.

[0013] The present invention also provides a method for preparing a hollow three-dimensional porous silicon material, comprising ball-milling silicon dioxide and magnesium silicide at a molar ratio of 1:0.8-1.5 until the magnesium silicide is evenly coated on the surface of the silicon dioxide to obtain a precursor mixture; then calcining the precursor mixture under an inert atmosphere at a calcination temperature of 500-750°C; then acid washing to remove the magnesium oxide, and then using hydrofluoric acid to remove the unreacted silicon dioxide in the core to obtain a hollow three-dimensional porous silicon material.

[0014] The present invention makes a breakthrough in using magnesium silicide as a reducing agent, and the reaction formula with silicon dioxide is as follows:

[0015] SiO2(s)+Mg2Si(s)→Si(s)+2MgO(s)

[0016] The theoretical heat release of the reaction is -214.001 kJ, while the theoretical heat release of magnesium thermal reaction using magnesium metal as a reducing agent is -576.094 kJ, and the heat release of the reaction is reduced by 62.9%. Magnesium silicide is the only stable compound in the Mg-Si binary system, with high hardness, high melting point, and high elastic modulus. It is observed under an electron microscope as an irregular block of 10-20 μm. After the calcination temperature exceeds 650°C, the magnesium in magnesium silicide will gradually melt out, and a porous silicon structure will be formed on the outer surface of the spherical shell of silica; at the same time, the melted liquid magnesium can react with the core of silica to produce Si and MgO. After pickling to remove MgO, three-dimensional porous silicon is further formed on the inner and outer surfaces of the shell. Finally, hydrofluoric acid is used to remove the incompletely reacted silica in the core to form a hollow structure, and a hollow three-dimensional porous silicon material is obtained.

[0017] In the ball milling step of the present invention, magnesium silicide needs to be uniformly coated on the surface of silicon dioxide. This step is an important part of obtaining the hollow three-dimensional porous silicon material of the present invention. Surprisingly, under the appropriate ratio of magnesium silicide and silicon dioxide, ball milling is carried out at a speed of 100-300rpm / min, and the ball milling time is 1.5-4 hours, which can achieve effective coating of silicon dioxide. Using an electron microscope to observe the precursor mixture after ball milling, it can be observed that the mixture is spherical, the particle size is similar to SiO2, the surface is rough, and the block shape of the magnesium silicide raw material cannot be found, indicating that the morphology of SiO2 is not destroyed during the ball milling process, and magnesium silicide is coated on the surface of SiO2. In order to further determine the composition and distribution in the ball milling mixture, it is known from the element distribution analysis in the transmission electron microscope that the orange Mg element is distributed outside the spherical particles, indicating that the position of Mg2Si is wrapped outside the particles; the red O element is distributed inside the particles, indicating that SiO2 is distributed inside the particles; and the yellow Si element is distributed throughout the particles. Therefore, it can be confirmed that Mg2Si does achieve effective coating of the outside of SiO2.

[0018] In order to provide a preferred ratio of silicon dioxide and magnesium silicide for ball milling, the molar ratio of silicon dioxide to magnesium silicide is 1:0.9-1.2. Using the method of the present invention, a small amount of magnesium will escape in gaseous form at high temperature and be carried away by the inert gas, so silicon dioxide is generally excessive; in order to ensure that the product has a hollow structure, the proportion of silicon dioxide generally needs to be excessive. The ratio of silicon dioxide to magnesium silicide also determines the thickness of the shell and the size of the hollow cavity. Therefore, further optimization of the molar ratio of raw materials and ball milling process can significantly improve the integrity and uniformity of the material morphology, and obtain a hollow silicon material with an ideal three-dimensional porous shell.

[0019] Therefore, as a preferred embodiment of the present invention, silicon dioxide and magnesium silicide are ball-milled in a molar ratio of 1:0.9-1.1 for 2-3 hours, and the temperature during ball milling is controlled not to exceed 100°C, until magnesium silicide is evenly coated on the surface of silicon dioxide to obtain a precursor mixture; then the precursor mixture is calcined in an inert atmosphere at a calcination temperature of 500-700°C for 2.5-6 hours. The inert atmosphere is argon, nitrogen, or a mixed gas of argon and nitrogen in any proportion.

[0020] Furthermore, the pickling is carried out by using a mixture of any one or more of hydrochloric acid, sulfuric acid, phosphoric acid, hydrofluoric acid, acetic acid and oxalic acid, with a concentration of 0.1-10 mol / L.

[0021] Furthermore, the concentration of the hydrofluoric acid is 0.1-10 mol / L and it is a necessary acid. Finally, the material is washed with water and dried to obtain a hollow three-dimensional porous silicon material.

[0022] The preparation method of the hollow three-dimensional porous silicon material provided by the present invention makes use of magnesium silicide as a reducing agent for the magnesium thermal reaction in a breakthrough manner. In the traditional magnesium thermal reaction, magnesium silicide is regarded as a by-product of the reaction, and SiH4 gas is generated during the acid washing and removal process, which is prone to explosion. If SiO2 is excessive during the reaction, a large amount of heat is released during the reaction, resulting in sintering and agglomeration, which seriously affects the cycle stability of the material and has a low yield.

[0023] If magnesium metal and silicon dioxide are ball-milled and then calcined, a porous structure can be formed, but the original spherical morphology of SiO2 cannot be maintained. In addition, without adding a heat-clearing agent, the product Si will sinter and agglomerate to form large particles of tens of microns, which will seriously damage its cycle stability.

[0024] The three-dimensional porous silicon material provided by the present invention has a porous structure on the outer surface of the shell layer formed by melting out magnesium under high-temperature calcination, while the porous structure on the inner surface is formed by removing magnesium oxide by pickling. The two processes together form a complex porous structure, which can obtain a specific surface area of ​​not less than 100m 2 / g, and an average thickness of 0.5-10μm spherical shell. By adjusting the raw material ratio and related process parameters, the shell thickness and hollow cavity morphology can be further optimized to obtain more than 120-150m 2 / g specific surface area and an average thickness of 0.5-7μm. The porous structure of the shell can provide a buffer space for the volume expansion of the silicon material, which is beneficial to improving the cycle stability of the silicon material. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a scanning electron microscope image of silicon dioxide in Example 1 of the present invention;

[0026] Figure 2 This is a scanning electron microscope image of magnesium silicide in Example 1 of the present invention;

[0027] Figure 3 This is a scanning electron microscope photograph of the mixture after ball milling in Example 1 of the present invention;

[0028] Figure 4 This is a photo of element distribution of the mixture after ball milling in Example 1 of the present invention;

[0029] Figure 5 This is a scanning electron microscope image of the hollow porous silicon in Example 1 of the present invention;

[0030] Figure 6 XRD diagrams of reactants and products of the present invention;

[0031] Figure 7 This is a graph showing the electrochemical performance of the hollow porous silicon of the present invention;

[0032] Figure 8 A scanning electron microscope image of porous silicon of a comparative example of the present invention;

[0033] Fig. 9 This is a graph showing the electrochemical performance of a comparative example of the present invention. DETAILED DESCRIPTION

[0034] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0035] Example 1

[0036] This embodiment provides a method for preparing a hollow three-dimensional porous silicon material, and the preparation method is as follows:

[0037] (1) Add silicon dioxide and magnesium silicide into a ball mill at a molar ratio of 1:1, and ball mill at a speed of 250 rpm / min for 3 hours to obtain a precursor mixture. During the ball milling process, the temperature does not exceed 100° C.

[0038] (2) The precursor mixture was calcined in an argon atmosphere at a temperature of 650° C. for 5 hours and then naturally cooled to room temperature.

[0039] (3) The product was acid-washed in 2 mol / L hydrochloric acid for 5 h and then centrifuged to obtain the solid.

[0040] (4) The solid obtained in step (3) is acid-washed in 2 mol / L hydrofluoric acid for 2 h and then centrifuged to obtain a hollow three-dimensional porous silicon material.

[0041] Figure 1 and Figure 2The morphology of silicon dioxide and magnesium silicide raw materials under electron microscope is shown respectively. It can be seen that SiO2 is spherical with a particle size distribution of 2-6 microns; magnesium silicide alloy is blocky with a particle size of 10-20 microns. The precursor mixture obtained after ball milling is observed under electron microscope as follows Figure 3 As shown, it can be seen that the precursor mixture after ball milling is spherical with a rough surface and a particle size similar to that of the raw silicon dioxide. The block shape of the magnesium silicide raw material is not found, indicating that the morphology of the raw silicon dioxide is not destroyed during the ball milling process, and the magnesium silicide is evenly coated on the surface of the silicon dioxide.

[0042] Figure 4 The element distribution analysis in the transmission electron microscope shows that the Mg element (orange) is distributed outside the spherical particles, indicating that the location of Mg2Si is wrapped outside the particles; the O element (red) is distributed inside the particles, indicating that SiO2 is distributed inside the particles; and the Si element (yellow) is distributed throughout the particles. Therefore, it can be confirmed that Mg2Si has indeed achieved effective coating of the outside of SiO2.

[0043] The hollow three-dimensional porous silicon material prepared by the above method is as follows Figure 5 As shown, the average particle size is 0.5-10μm and the specific surface area is 120-150m 2 / g, having a porous spherical shell with an average thickness of 0.5-10μm and high shell integrity. Figure 6 The XRD diagram of the material is shown, showing that silicon dioxide is an amorphous phase, magnesium silicide is crystalline, and the reaction ultimately yields a pure phase silicon material.

[0044] This material can be used to prepare the negative electrode of lithium battery. The above-mentioned hollow three-dimensional porous silicon, acetylene black and adhesive are mixed in a mass ratio of 8:1:1, and an appropriate amount of water is added to prepare a slurry. The slurry is coated on the current collector copper foil and dried at 60°C for 10 hours under vacuum conditions to obtain a pole piece. Metal lithium sheets are used as counter electrodes and reference electrodes, 1M LiPF6 is dissolved in a mixed solution of EC / DEC (volume ratio 1:1) as an electrolyte, and button cells are assembled in an argon glove box. The assembled button cells are charged and discharged at a certain current density in the voltage range of 0.01-1V. The electrochemical properties are as follows: Figure 7 As shown, at 0.5A g -1 The capacity after 200 cycles at the current density is 2384.1 mAh g -1 , the capacity retention rate is 86.4%.

[0045] Example 2

[0046] The preparation method of the hollow three-dimensional porous silicon material provided in this embodiment is as follows:

[0047] (1) Add silicon dioxide and magnesium silicide into a ball mill at a molar ratio of 1:0.8, and ball mill at a speed of 100 rpm / min for 3 hours to obtain a precursor mixture. During the ball milling process, the temperature does not exceed 100° C.

[0048] (2) The precursor mixture was calcined in an argon atmosphere at a temperature of 750° C. for 5 hours and then naturally cooled to room temperature.

[0049] (3) The product was acid-washed in 2 mol / L hydrochloric acid for 5 h and then centrifuged to obtain the solid.

[0050] (4) The solid obtained in step (3) is acid-washed in 2 mol / L hydrofluoric acid for 2 h and then centrifuged to obtain a hollow three-dimensional porous silicon material.

[0051] The negative electrode of a lithium battery was prepared using the material according to the method in Example 1. -1 The capacity after 200 cycles at the current density is 1976.5 mAh g -1 , the capacity retention rate is 77.2%.

[0052] Example 3

[0053] The preparation method of the hollow three-dimensional porous silicon material provided in this embodiment is as follows:

[0054] (1) Add silicon dioxide and magnesium silicide into a ball mill at a molar ratio of 1:1.1, and ball mill at a speed of 300 rpm / min for 3 hours to obtain a precursor mixture. During the ball milling process, the temperature does not exceed 100° C.

[0055] (2) The precursor mixture was calcined in an argon atmosphere at a temperature of 700° C. for 5 hours. After the calcination, the mixture was naturally cooled to room temperature.

[0056] (3) The product was acid-washed in 2 mol / L hydrochloric acid for 5 h and then centrifuged to obtain the solid.

[0057] (4) The solid obtained in step (3) is acid-washed in 2 mol / L hydrofluoric acid for 2 h and then centrifuged to obtain a hollow three-dimensional porous silicon material.

[0058] The negative electrode of a lithium battery was prepared using the material according to the method in Example 1. -1 The capacity after 200 cycles at the current density is 1878.1 mAh g -1 , the capacity retention rate is 73.7%.

[0059] Comparative Example

[0060] (1) Add silicon dioxide and magnesium powder in a molar ratio of 1:1 into a ball mill, and ball mill at a speed of 250 rpm / min for 3 hours to obtain a precursor mixture.

[0061] (2) The precursor mixture was calcined in an argon atmosphere at a temperature of 650° C. for 5 hours and then naturally cooled to room temperature.

[0062] (3) The product was acid-washed in 2 mol / L hydrochloric acid for 5 h and then centrifuged to obtain the solid.

[0063] (4) The solid obtained in (3) was acid-washed in 2 mol / L hydrofluoric acid for 2 h and then centrifuged to obtain a silicon material.

[0064] Figure 8 This is the morphology of the silicon material obtained by using magnesium metal as a reducing agent under an electron microscope in this example, and agglomeration caused by high temperature sintering can be seen. The negative electrode of a lithium battery was prepared using this material according to the method in Example 1, and the assembled battery was charged and discharged at a certain current density in the voltage range of 0.01-1V. The electrochemical performance is shown in FIG. Fig. 9 As shown, at 0.5Ag -1 The capacity after 200 cycles at the current density is 1747.2 mAh g -1 , the capacity retention rate is 70.8%.

[0065] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a hollow three-dimensional porous silicon material, characterized in that: The silicon dioxide and magnesium silicide are ball-milled at a molar ratio of 1:0.8-1.5 until the magnesium silicide is evenly coated on the surface of the silicon dioxide to obtain a precursor mixture; the silicon dioxide and magnesium silicide are ball-milled at a rotation speed of 100-300 rpm for 1.5-4 hours; the temperature during ball milling does not exceed 100°C; The precursor mixture is then calcined in an inert atmosphere at a temperature of 500-750° C.; the magnesium oxide is then removed by pickling, and the unreacted silicon dioxide in the core is removed by hydrofluoric acid to obtain a hollow three-dimensional porous silicon material; The hollow three-dimensional porous silicon material includes an average particle size of 0.5-10 μm and a specific surface area of ​​100-200 m 2 / g of hollow silicon.

2. The method for preparing a hollow three-dimensional porous silicon material according to claim 1, characterized in that: The molar ratio of silicon dioxide to magnesium silicide is 1:0.9-1.

2.

3. The method for preparing a hollow three-dimensional porous silicon material according to claim 1, characterized in that: The inert atmosphere is argon, nitrogen, or a mixed gas of argon and nitrogen in any proportion.

4. The method for preparing a hollow three-dimensional porous silicon material according to claim 1, characterized in that: The calcination time is 2.5-6 hours.

5. The method for preparing a hollow three-dimensional porous silicon material according to claim 1, characterized in that: The pickling is carried out by mixing any one or more of hydrochloric acid, sulfuric acid, phosphoric acid, hydrofluoric acid, acetic acid and oxalic acid, with a concentration of 0.1-10 mol / L.

6. A hollow three-dimensional porous silicon material, characterized in that: Prepared by the method according to claim 1, the hollow silicon has a complete or incomplete spherical shell layer with an average thickness of 0.5-10 μm, and the shell layer is a three-dimensional porous structure.

7. The hollow three-dimensional porous silicon material according to claim 6, characterized in that: The material includes an average particle size of 2-8 μm and a specific surface area of ​​120-150 m 2 / g of hollow silicon, wherein the hollow silicon has a complete or incomplete spherical shell layer with an average thickness of 0.5-7 μm.

8. The hollow three-dimensional porous silicon material according to claim 7, characterized in that: The material includes 90-99% by mass of hollow silicon and 1-10% by mass of oxygen, with an average particle size of 0.5-10 μm and a specific surface area of ​​120-150 m 2 / g.

9. A negative electrode for a lithium battery, comprising a current collector coated with a slurry and dried, wherein the slurry comprises, by mass percentage, 80-98% of the hollow three-dimensional porous silicon material as claimed in claim 6, 0.1-10% of a conductive agent, and 0.1-10% of a binder.